2020
DOI: 10.1021/acs.est.0c05399
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Oxidative Degradation Mitigated the Developmental Toxicity of Polyamide Microplastics to Zebrafish Larvae by Modulating Macrophage-Triggered Proinflammatory Responses and Apoptosis

Abstract: Microplastics (MPs) are ubiquitous in the environment and pose substantial threats to the water ecosystem. However, the impact of natural aging of MPs on their toxicity has rarely been considered. This study found that visible light irradiation with hydrogen peroxide at environmentally relevant concentration for 90 days significantly altered the physicochemical properties and mitigated the toxicity of polyamide (PA) fragments to infantile zebrafish. The size of PA particles was reduced from ∼8.13 to ∼6.37 μm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Although data are scarce and our knowledge is based exclusively on pure polymers, the impacts of photochemical weathering appear to be mixed. A couple of studies reported that exposure of plastic to sunlight increased toxicity, , one reported no major impact, and another reported decreased toxicity . Our collective findings indicate that a comprehensive and accurate understanding of the fate and impacts of marine plastic pollutiona critical step toward establishing evidence-based policies and developing next-generation materialsrequires the research community to embrace the diverse formulations and sunlight-driven transformations of plastics in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although data are scarce and our knowledge is based exclusively on pure polymers, the impacts of photochemical weathering appear to be mixed. A couple of studies reported that exposure of plastic to sunlight increased toxicity, , one reported no major impact, and another reported decreased toxicity . Our collective findings indicate that a comprehensive and accurate understanding of the fate and impacts of marine plastic pollutiona critical step toward establishing evidence-based policies and developing next-generation materialsrequires the research community to embrace the diverse formulations and sunlight-driven transformations of plastics in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…For infantile zebrafish, bioaccumulation of weathered polyamide particles (treated with hydrogen peroxide alone or with light irradiation) was less explicit than for the pristine material. 36 Furthermore, the digestive action of marine invertebrates has been demonstrated to facilitate fragmentation of plastic particles to smaller size ranges 37,38 and to provide a pathway for sinking by the excretion of faecal matter aggregates. 39 Time Scales of Plastic Weathering.…”
Section: ■ Exposure and Weatheringmentioning
confidence: 99%
“…The main mechanism of degradation could involve chemical, physical, biological or a combination of those processes. More specifically, polymeric degradations playing role on microplastic formation can be listed as thermal, mechanochemical, ozone-induced, biological, photo-oxidative, and catalytic types of processes [ 39 , 40 ], and interestingly, these processes seem to influence their toxicity as well [ 26 , 41 ]. O’Kelly et al [ 15 ] stated that ozone-induced degradation, biodegradation and photo-oxidative degradation are the main degradation types contributing to breaking down the “macro” and “meso” plastics and consequently forming microplastics in soils.…”
Section: Formation and Existence Of Microplastics In Soilsmentioning
confidence: 99%